Does vitamin D level have an effect on COVID-19 positivity and COVID-19 related mortality? A retrospective study - Goktas, Olgun; Ercan, Ilker; Canan Ersoy; Arda Uzunoglu; Fatma Ezgi Can (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the possible relationship between vitamin D and coronavirus disease-2019 in an urban population known to have relatively low vitamin D levels. Method: The retrospective study was conducted in Bursa, Turkey, and comprised data of 30 family health centers from March 1 to December 15, 2020, related to diagnosed inpatients of coronovairus disease-2019. The diagnosis was based on polymerase chain reaction test for severe acute respiratory syndrome coronavirus-2 infection. Vitamin D levels of these patients were obtained from previous records and compared with those without polymerase chain reaction positivity. Vitamin D levels of positive patients who survived were compared with those who died of coronavirus disease-2019. Data was analysed using SPSS 21. Result: Of the 2,105 patients whose data was retrived, 212(10%) were positive for coronavirus disease-2019, while 1,893(90%) were negative. Among the positive patients, 89(42%) were men and 123(58%) were women. The overall median age was 45 years (Q1-Q3(Q1: first quartile, Q3: third quartile): 35-56 years). Vitamin D level was not significantly different between the positive and negative patients (p>0.05). Among the positive patients, 2(0.9%) patients did not have new admissions to the designated centers and their data was excluded, 206(97.2%) survived and 4(1.9%) died. There was no significant difference in vitamin D levels between those who survived and those who died (p>0.05). Conclusion: There was no significant relationship found between vitamin D levels and coronavirus disease-2019 infection and related deaths. Key Words: COVID-19, PCR positivity, SARS-CoV-2 infection, Vitamin D.